Evaluation of feed flow rate on the physicochemical properties of fish oil microcapsules - Hashim, N. A.; Abdul Mudalip, S. K.; M. Arshad, Z. I.; Che Man, R. (School of Engineering, Taylor’s University, 2023)
Fish oil is one of the sources of fatty acids and plays a significant role in maintaining a healthy lifestyle. Regular intake of fish oil can prevent cardiovascular-related disease and improve the development of infants' and young children's brain functions. However, fish oil is highly prone to oxidative deterioration, leading to higher shelf-stability reduction. Microencapsulation by spray drying technology offers a better solution by protecting the oil from further oxidation, enabling it to be delivered to food products without affecting its properties. The present study focuses on the physicochemical properties of fish oil microcapsules by spray drying techniques with different feed flow rates. The feed flow rate studied was 280 mL/h to 444 mL/h, combining maltodextrin and whey protein isolates as biopolymers. The physicochemical properties evaluated were moisture content, particle size distribution, free fatty acid, acid value and encapsulation efficiency. This work aimed to identify the most suitable feed flow rate based on the evaluated physicochemical properties. It was observed that the moisture content and particle size distribution were increased from 3.15  0.01 % to 3.54  0.06 % and 27.621  0.320 μm to 50.636  1.321 μm from the feed flow rate of 280 mL/h to 444 mL/h, respectively. The fish oil microcapsules produced using a feed flow rate of 280 mL/h recorded the highest free fatty acid, acid value and encapsulation efficiency of 5.11  0.101 %, 2.82  0.004 mg (KOH/g) and 80.89  0.231 %. Thus, it can be suggested that spray drying with a low feed flow rate of 280 mL/h can produce fish oil microcapsules with a lower moisture content, particle size distribution, free fatty acid, and acid value with higher encapsulation efficiency.